2017
DOI: 10.11613/bm.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

The role of laboratory testing in detection and classification of chronic kidney disease: national recommendations

Abstract: Chronic kidney disease (CKD) is a common clinical condition with significant adverse consequences for the patient and it is recognized as a significant public health problem. The role of laboratory medicine in diagnosis and management of CKD is of great importance: the diagnosis and staging are based on estimation of glomerular filtration rate (eGFR) and assessment of albuminuria (or proteinuria). Therefore, the joint working group of the Croatian society of medical biochemistry and laboratory medicine and Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
(50 reference statements)
0
19
1
Order By: Relevance
“…Biljak et al reported 6 key factors for laboratories implementing the national guidelines for the diagnosis and management of CKD. The first factor is good communication between laboratory and clinicians ( 22 ). We also share the opinion that open and frequent communication is important for any guideline implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Biljak et al reported 6 key factors for laboratories implementing the national guidelines for the diagnosis and management of CKD. The first factor is good communication between laboratory and clinicians ( 22 ). We also share the opinion that open and frequent communication is important for any guideline implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Test reports should include the test result and the type of fluid analysed ( 5 , 10 ). Laboratories should provide clinical decision limits and interpretive information with each pleural fluid test result to guide clinical interpretation and decision-making (Table 3 and Appendix 2) (Class 1) ( 2 , 5 , 18 , 23 ).…”
Section: Serous Fluids Analysismentioning
confidence: 99%
“…The linearity problem of protein measurement and hook effect in albumin measurement from body fluids S erum total protein (sPRT) and serum albumin (sALB) tests and micro total protein (MTP) and micro albumin (MA) tests for various body fluids are routinely performed in clinical biochemistry laboratories. These analyses are crucial for screening kidney pathologies from urine samples and for their diagnosis, prognosis, and treatment planning [1]; for differentiating exudate and transudate from pleural fluids [2]; and for investigating central nervous system infections and assessing blood-brain barrier functions from the cerebrospinal fluid (CSF) [3]. Levels of sPRT and sALB are high enough to be expressed in grams, and they vary in a certain range.…”
Section: Letter To the Editormentioning
confidence: 99%